Implementing ITI for urban development locally - Garyfallia Katsavounidou (TeMA: Journal of Land Use, Mobility and Environment, 2017)
In the current Programming Period (2014-2020) the European Commission has introduced a new strategic instrument, the Integrated Territorial Investment (ITI), which shifts the decisions on allocation of funds to the local level and, most importantly, enables drawing of funds from several priority axes and from several European Structural and Investment Funds. Greece is one of EU member countries that has committed on using ITIs as a tool for urban development. In August 2016, in the Region of Central Macedonia, urban authorities with a population of over 10.000 inhabitants were invited by the Managing Authority of the Regional Operational Programme to submit a Strategy for Sustainable Urban Development (SUD), through the mandatory implementation of the ITI tool. The paper focuses on one of these municipalities, the city of Veria, where the ITI approach has been implemented for the design of an ITI of urban scale (ITI-SUD). The integrated approach prescribed by regional authorities forced Municipalities to adopt government approaches uncommon until now: to involve multiple stakeholders in the entire process, from strategy development to project selection and implementation. The paper describes the benefits and challenges of the new approach as applied in the local context, showing the vertical and horizontal connections of urban development strategies. Most importantly, in the context of ‘procedural learning’ happening in Europe in the field of territorial cohesion, it offers an insight on how European cohesion policy strategies and tools are tested at the local level.